Ensaios sobre produtividade e eficiência agropecuária: América Latina e Nordeste do Brasil - Reis, Lucas David Ribeiro (2019)
This paper is composed of two articles dealing with the question of productivity and efficiency of agriculture. In the first article, the objective was to study the technical efficiency and the total productivity of agricultural factors in the countries of Latin America and the Caribbean. For this, the stochastic production frontier approach and the Malmquist productivity index were used. The data on value of production and the quantity of agricultural inputs covered the years 1991 to 2012. The results showed that all countries presented technical inefficiency of agricultural production over the period. The variables that significantly explained the inefficiency of agricultural production were credit and energy consumption in agriculture, which represented an innovation in this area. The Malmquist productivity index showed that there were gains in total factor productivity, which were attributed to the variation in the technical efficiency of production. The second article was focused on evaluating and comparing the efficiency of the agricultural sector of the northeastern states in order to capture differences in the productivity of agricultural production factors. For this, data extracted from the Agricultural and Livestock Census of the years 1996 and 2006 were used to construct a panel of agricultural production data at municipal level. The analyzes of the efficiency of agricultural production were made based on stochastic frontier and meta-frontier analyzes. The results showed that the agricultural sector presented technical inefficiency in all the states, which differed in the technological level, which justified the estimation of the meta-frontier function. Although with low levels, Bahia, Pernambuco and Maranhão were the states with the highest technical efficiency indexes.